112k views
3 votes
Multiply -7(y-1) what's the answer

User Bradmo
by
5.8k points

1 Answer

2 votes

We have the following equation.


-7(y-1)

To multiply we operate each term of the parenthesis by the -7, in addition, we also operate the signs.


\begin{gathered} -7(y-1)=-7y+7 \\ \end{gathered}

If you are looking to solve for "y" what we need to do is clear it.


\begin{gathered} -7y+7=0 \\ 7y=7 \\ y=(7)/(7) \\ y=1 \end{gathered}

In conclusion, the multiplication is:


-7y+7

The value to "y" is


y=1

User BogdanBiv
by
5.2k points